The Effect of Urbanization and Industrialization on Energy Use in Emerging Economies: Implications for Sustainable Development. (April 2014) - Sadorsky, Perry
Abstract This article investigates the impact of two important socio‐economic variables—urbanization and industrialization—on energy consumption in a panel of emerging economies. The results indicate that income increases energy consumption in both the long run and the short run. In the long run, urbanization decreases energy consumption, while industrialization increases it. Long‐run dynamics are important as evidenced by the estimated coefficient on the error correction term. These results have implications for sustainable development. Economic growth policies designed to increase income and industrialization will increase energy consumption. Since most energy needs in emerging economies are currently met by the burning of fossil fuels, economic growth and industrialization policies will be at odds with sustainable development.